HUBUNGAN FILSAFAT PENDIDIKAN DAN FILSAFAT MATEMATIKA DENGAN PENDIDIKAN - Venny Herawati Simangunsong (Sepren, 2021)
Etymologically (meaning according to the word) the term philosophy comes from the Greek philosophia. This word is a compound word philos which means lover or friend of knowledge, and sophia which means wisdom or wisdom. Whereas mathematics has long been considered the most familiar source of certain knowledge to mankind. The word mathematics comes from the Latin word mathematics which was originally taken from the Greek word mathematike which means studying. Philosophy of educational disciplines is metadisiplinary, in the sense that it relates to concepts, ideas, and methods of educational science. Education requires a philosophy because educational problems are not only related to the implementation of education which is limited by experience, but wider, deeper, and more complex problems, which are not limited by experience or educational facts, and cannot be reached by educational science. . Educational philosophy must be able to provide guidance to educators (teachers). This will color their behavior in managing the teaching and learning process (PBM). In addition, understanding the philosophy of education will keep them from groping, trying without planning in solving educational problems.